2005
DOI: 10.1128/aac.49.6.2218-2225.2005
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Molecular Characterization of Mycobacterium tuberculosis Isolates Resistant to both Isoniazid and Ethambutol

Abstract: In performing radiometric susceptibility testing on over 2,000 patient isolates of Mycobacterium tuberculosis during the past 6 years, we found that resistance to 7.5 g/ml ethambutol (EMB) occurred only in isolates that are also resistant to 0.4 g/ml isoniazid (INH). Using 157 selected isolates in the present study, we performed radiometric and agar proportion susceptibility tests and DNA sequencing of genetic regions associated with resistance to these two drugs. The goal was to study the occurrence of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 37 publications
8
53
2
Order By: Relevance
“…Some authors also propose that embB codon 306 mutations are associated with resistance to other antituberculosis drugs and with MDR M. tuberculosis. This fact underlines a more general impact of this mutation on drug resistance (6,14). More extensive and detailed studies in different settings are needed to clarify this.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors also propose that embB codon 306 mutations are associated with resistance to other antituberculosis drugs and with MDR M. tuberculosis. This fact underlines a more general impact of this mutation on drug resistance (6,14). More extensive and detailed studies in different settings are needed to clarify this.…”
Section: Discussionmentioning
confidence: 99%
“…Since 43.8% (71/162) of our EMB-resistant isolates exhibited WT patterns when using the GenoType MTBDRsl test alone, 9 isolates harbored mutations in the embA, embC, and embR genes. In addition, some reports have suggested that embB codon 306 mutations do not confer resistance to EMB but rather constitute a common polymorphism of the susceptibility to develop any type of drug resistance or MDR (9,18,22,27). Although those reports offer speculation on the biological role of this mutation (3), further studies are needed to identify actual mechanisms of EMB resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This depends on EMB resistance mechanisms. EMB resistance is regulated by both gene mutations and gene expression (51). embB 306, 406, and 497 were only shown to be associated with embB mutations and EMB resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the embB 306 mutation is the mutant hot site in EMB-resistant strains (45-48), it was not enough to cover a single detection site for embB 306 (50,51). Other studies used multiple sites of the embB gene as detection sites when using molecular detection techniques (16,17,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%